Analisis Penyampaian Materi Sejarah Lokal Kalimantan Barat Dalam Pembelajaran Sejarah Pada Peserta Didik Di SMAN 8 Pontianak - Dekari Endru Laja; Ika Rahmatika Chalimi; Haris Firmansyah (Mathematics Education Study Program, 2025)
This research aims to reveal West Kalimantan local history material to students in learning history at Senior High School 8 Pontianak. This research uses qualitative research with a case study approach. Data sources in this research include interviews with history teachers and class X students at SHS 8 Pontianak as well as teaching modules. Data collection was carried out through observation, interviews and documentation. The stages of data analysis include data collection, data reduction, data presentation, and verification/drawing conclusions. Data validity techniques use source triangulation and technical triangulation. The research results show: 1. There are four stages of planning for the delivery of West Kalimantan local history material which includes the implementation urgency stage, design, material selection, adjustments to teaching modules, and schedule adjustments. 2. Application of delivery of local history material and its evaluation. 3. Obstacles encountered in implementing the delivery of local history material in West Kalimantan, such as local historical sources that are difficult to obtain and the location of historical sites that are far from schools or where students live.